Pembelajaran PAI Berbasis Canva untuk Meningkatkan Minat Belajar Siswa di SMA Muhammadiyah 3 Jember - Nur Dzaedzatul H; Khozin Khozin (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This research aims to describe the implications of using Canva media in increasing students' interest in learning in class X in the subject of using Canva media in increasing the learning motivation of class This research uses a qualitative approach using the case study method, which provides descriptive data about the reality in the field using observation, interviews and documentation instruments. The research subjects were class X students at SMA Muhammadiyah 3 Jember. The object is the PAI teacher at SMA Muhammadiyah 3 Jember. The use of Visual Learning Media Based on the Canva Application makes children more active and enthusiastic in learning, because the appearance of Canva media is attractive, the images and colors are appropriate and attracts children's interest in learning which is supported by children's curiosity about this visual media is very high, so that children don't get bored of learning. So it can be concluded that the research results are expected to show that the use of Canva-based learning media can increase students' interest in learning. in PAI subjects."